Implementasi Model Problem Based Learning Untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik Pada Pelajaran Administrasi Jaringan - Ardian Prasetyo, Wira (Civil Officium: Journal of Empirical Studies on Social Science, 2021)
This study aimed to determine the increase in student activity and learning outcomes through the implementation of the Problem Based Learning (PBL) learning model. This research is classroom action research conducted in 2 cycles. The method of data collection was carried out through observation. Data analysis was carried out by comparing the test results in cycle 1 and cycle 2 with descriptive techniques after implementing the learning method using the Problem Based Learning model. Students' activeness can be seen from the aspect of students who give full attention to the material, dare to ask the teacher, answer questions, and have opinions. In addition, students also collaborate in groups, work on questions, learn to use resources, and make group presentations. This study indicates that the learning outcomes and learning activities of class XII students of SMK PUSTEK BSD, South Tangerang City, Banten Province, in the Basic Network Administration subject have increased.